"Overcoming the Limits". The first results of an interdisciplinary scientific project. Issue 1 (1st October 2022) - Andreev, A I; Grinin, A L; Ivanov, D V; Popov, V N
Abstract: The title of our this plenary presentation, "Overcoming the Limits", certainly echoes Meadows' famous "The Limits to Growth, " which has played a prominent role in understanding the path of humanity towards the future. However, during the past fifty years both the concept and understanding of these limits have significantly changed. In this report, the concept of limits is understood more broadly then usual. It includes not only the process of overcoming the limits that hinder development, but also implies situations when such limits become irrelevant. Another important point of our title is that limits are not insurmountable. To put it more precisely, they are serious but solvable challenges which can and should be resolved. This paper reflects the concept, developed by the research team of Moscow State University, on the prospects of future world development.